2017
DOI: 10.1039/c6ra26016k
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced degradation of gaseous benzene by a Fenton reaction

Abstract: A wet scrubbing process coupled with advanced oxidation processes (AOP) has raised great interest for the abatement of volatile organic compounds (VOCs) owing to its strong oxidation capacity and few byproducts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…6,7 It has been reported that the free radicals can convert benzene into phenol or other oxidation products. 18,19 Thus, it is expected that benzene adsorbed on the naturally Fe-containing activated carbon samples can be hydroxylated or oxidized through the Fenton reaction during treatment with the H 2 O 2 solution (eqn(1)-(3)). Fig.…”
Section: Characterization Of the Treated Activated Carbon Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…6,7 It has been reported that the free radicals can convert benzene into phenol or other oxidation products. 18,19 Thus, it is expected that benzene adsorbed on the naturally Fe-containing activated carbon samples can be hydroxylated or oxidized through the Fenton reaction during treatment with the H 2 O 2 solution (eqn(1)-(3)). Fig.…”
Section: Characterization Of the Treated Activated Carbon Samplesmentioning
confidence: 99%
“…31 Thus, during treatment with the H 2 O 2 solution, benzene adsorbed on the naturally Fe-containing activated carbon samples can be hydroxylated or oxidized to phenol or other oxidation products. 18,19 It was reported that H 2 O 2 on activated carbon could be decomposed into hydroxyl groups based on the Haber-Weiss mechanism and that the formation rate of hydroxy radicals at pH > 8.0 might be low. [32][33][34] Activated carbon + H 2 O 2 / activated carbon + + OH À + cOH (4)…”
Section: Benzene Decompositionmentioning
confidence: 99%
See 1 more Smart Citation
“…5b). With the increas of phenol, in addition to the initial benzene, phenol became another target compound for HO • , and resulted in the increase of catechol and hydroquinone [40,51]. Since catechol and hydroquinone have the ability to reduce the initial Fe(III) to Fe(II), Fe(II) recovery (Fig.…”
Section: H 2 O 2 Variation In Thementioning
confidence: 99%
“…These typical pollution sources including painting plants, petrochemical factories, and building materials factories in industrial parks normally make up a major proportion of the total odor pollutants emission, and they also occupy an irreplaceable role in promoting the city’s economy development [ 3 ]. Against this background, specific air monitoring systems and waste gas management methods have been abundantly developed to balance it out [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%